2010
DOI: 10.1002/jhet.481
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 3‐amino‐4,6‐dimethyl‐1H‐pyrazolo[3,4‐b]pyridine in heterocyclic synthesis

Abstract: This review describe the synthesis and reactions of 3-amino-4,6-dimethyl-1H-pyrazolo[3,4-b]pyridine as building block for the synthesis of polyfunctionalized heterocyclic compounds with pharmacological interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Thus, 2-cyano-N-(4-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)-2-thioxothiazol-3(2H)-yl)a cetamide (5c) was reacted with (E)-3-(dimethylamino)-1-(furan-2-yl)prop-2-en-1-one (12) in ethanol catalysed by aceticacid to afford N-(4- (1,5- On the other hand, compound 2-cyano-N-(4-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)-2-t hioxothiazol-3(2H)-yl) acetamide 5c was reacted with a mixture of reacted with a mixture of malononitrile and elemental sulfur to afford 2,4-diamino-5-cyano-N-(4-(1, 5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl) -2-thioxothiazol-3-(2H)-yl)thiophene-3-carboxamide (19) Compound 19 is proposed to be formed by adding the active methylene group in malononitrile to the cyano In recent puplications , it has been reported that [5,10], diazotized aminopyrazoles or arene diazonium salts were used as starting materials for synthesis of pyrazolotriazines [5,10]. In the present work, diazotized 4-(5-amino-1H-pyrazol-3-yl)-1,5-dimethyl-2-phenyl-1H-pyrazol-3(2H)-one (20) [11,12] …”
Section: Resultsmentioning
confidence: 99%
“…Thus, 2-cyano-N-(4-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)-2-thioxothiazol-3(2H)-yl)a cetamide (5c) was reacted with (E)-3-(dimethylamino)-1-(furan-2-yl)prop-2-en-1-one (12) in ethanol catalysed by aceticacid to afford N-(4- (1,5- On the other hand, compound 2-cyano-N-(4-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)-2-t hioxothiazol-3(2H)-yl) acetamide 5c was reacted with a mixture of reacted with a mixture of malononitrile and elemental sulfur to afford 2,4-diamino-5-cyano-N-(4-(1, 5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl) -2-thioxothiazol-3-(2H)-yl)thiophene-3-carboxamide (19) Compound 19 is proposed to be formed by adding the active methylene group in malononitrile to the cyano In recent puplications , it has been reported that [5,10], diazotized aminopyrazoles or arene diazonium salts were used as starting materials for synthesis of pyrazolotriazines [5,10]. In the present work, diazotized 4-(5-amino-1H-pyrazol-3-yl)-1,5-dimethyl-2-phenyl-1H-pyrazol-3(2H)-one (20) [11,12] …”
Section: Resultsmentioning
confidence: 99%
“…All reactions were followed by TLC (Silica gel, Merck). 3-Amino-4,6-dimethyl-1 H -pyrazolo[3,4- b ]pyridine 1a [32], 3-amino-4,6-diphenyl-1 H -pyrazolo[3,4- b ]pyridine 1b [33] and hydrazonoyl halides 2 [34,35] were prepared as reported in the literature.…”
Section: Experimental Protocolsmentioning
confidence: 99%